Antimicrobial Finish for Cotton/polyester from Natural Bio-extracts - Sadaf, Shama; Hassan, Komal; Saeed, Ayesha; Ahmad, Zeeshan (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
This study develops and applies sustainable antimicrobial finishes derived from Azadirachta indica (Neem), Butea monosperma, and Litchi chinensis leaf extracts to 50/50 cotton/polyester blend fabrics. The antimicrobial efficacy of these finishes was evaluated, revealing a 100% reduction in microbial growth after 22 hours and six days. Before and after applying antimicrobial finish FTIR, SEM and fabric aesthetic properties were checked. The antimicrobial finish was applied by the pad dry cure method and finish was fixed by using of polyurethane binder. In case of aesthetic properties (stiffness, smoothness appearance) antimicrobial finish had positive effect on 50/50 cotton/polyester. The treated fabrics also exhibited significant increases in stiffness (p < 0.001, h2 = 0.85). Additionally, the smoothness appearance of treated fabrics was assessed, revealing a slight decrease in smoothness appearance ratings as compared to untreated controls group, although this decrease was not statistically significant (p = 0.29). Fourier Transform Infrared (FTIR) spectroscopy revealed changes in functional groups, indicating successful finish application. Scanning Electron Microscopy (SEM) micrographs displayed surface modifications and filament breakage. The results were analyzed through ANOVA. The fabric properties were checked by using AATCC standard test methods. These eco-friendly finishes offer promising alternatives to synthetic antimicrobials, enhancing textile sustainability and consumer safety. The findings of this study contribute to the development of sustainable and environmentally friendly textile finishes.